Chinese morphological awareness assessment and its relation to reading acquisition: a cross-cultural meta-analysis - Sihui Ke (Humanities & Social Sciences Communications)
Abstract Morphological awareness involves understanding of morphemes and intraword morphological structure. This meta-analysis adopted a cross-cultural perspective to examine the strengths of correlations between morphological awareness assessment and a range of reading outcomes (word decoding, vocabulary, and reading comprehension) in morphosyllabic Chinese, highlighting the nuanced role of morphological awareness in Chinese reading development for different learner populations. A total of 204 studies with 257 independent samples were included for a meta-analysis of coefficients and meta-regression. The samples involved 42,517 learners of Chinese as a first-language (L1) or a second-language (L2) from Chinese culture immersive contexts and non-immersive contexts. Results showed small to moderate correlations between morphological awareness and reading skills for L1 learners in immersive contexts, with culture having a stronger moderating effect than assessment. For L2 learners, moderate and significant correlations were found between morphological awareness and reading subskills, with both assessment and culture acting as independent and significant moderators.